2021
DOI: 10.1021/acs.jchemed.0c01179
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Chemistry to Mathematics by Establishing the Relationship between Conductivity and Concentration in an Interdisciplinary, Computer-Based Project for High School Chemistry Students

Abstract: Here, we present an interdisciplinary educational project intended for high school chemistry that is focused on the establishment of a mathematical model to describe the relationship between conductivity and concentration, while linking chemistry to mathematics with the help of computer software. The project was designed to help high school students engage in methods and comprehend advanced topics beyond the typical high school chemistry curriculum, as well as to resolve a problem that no single disciplinary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…In addition, basic computer skills are involved such as setting up an algorithm, as part of computational thinking. In general, it has been shown that computer simulations are useful in chemical education. , Here, it is expected that models, which make it possible to go beyond a black-box simulations and confront the students with setting up an algorithm for the chemical process, deepen the understanding of the phenomena further. Finally, computer simulations are today widely spread in chemical science, and students should get the opportunity to become acquainted with such methods in an early general chemical education including upper secondary education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, basic computer skills are involved such as setting up an algorithm, as part of computational thinking. In general, it has been shown that computer simulations are useful in chemical education. , Here, it is expected that models, which make it possible to go beyond a black-box simulations and confront the students with setting up an algorithm for the chemical process, deepen the understanding of the phenomena further. Finally, computer simulations are today widely spread in chemical science, and students should get the opportunity to become acquainted with such methods in an early general chemical education including upper secondary education.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it has been shown that computer simulations are useful in chemical education. 35,36 Here, it is expected that models, which make it possible to go beyond a black-box simulations and confront the students with…”
Section: ■ Discussionmentioning
confidence: 99%
“…The model making of the environmental art design course is all done by hand. The workload from design to model completion is very large [10]. Therefore, the assignment in the environmental art design course requires several students to cooperate to give full play/potential according to the characteristics of each person.…”
Section: Significance Of the Application Of Model Space Research Methodsmentioning
confidence: 99%
“…While addressing the informal REs conducted for school students in science, technology, engineering, and mathematics (STEM) integrated curriculum, STEM driven REs have been practiced under different summer programs with the aim of promoting the students to choose STEM disciplines at universities. STEM-driven REs is also successful in influencing students to retain their undergraduate courses in STEM majors in addition to encouraging fewer dropouts or major changes. ,, One of the main aims of subjecting students to STEM driven Research Experience Programs (REP)­s is to impart the multidisciplinary relations between the different disciplines like chemistry, biology, mathematics, physics, engineering, and technology that come across in each research project . The students are resultantly introduced to the benefits of the multidisciplinary approach adopted by the STEM driven REPs and training to tackle problems with solutions integrated from multiple disciplines. …”
Section: Introductionmentioning
confidence: 99%
“…However, studies were limited around analyzing the impact of chemistry-based RE at school settings in effectively contributing to high school students’ research competency and self-efficacy development. Limited studies employed direct assessment methods to analyze the effect of innovative chemistry research-based teaching practices that recorded the university students’ overall development. ,, Most of these studies were also successful to an extent in demonstrating the role of chemistry in enhancing 21st-century skills as required by the demanding higher institutions, research community, and STEM labor market. However, students’ self-perceptions were not studied distinctly to assess the impact of innovative teaching practices that employed high school chemistry.…”
Section: Introductionmentioning
confidence: 99%